Lingual concavities in the mandible: a morphological study using cross-sectional analysis determined by CBCT - Nickenig, Hans-Joachim; Wichmann, Manfred; Eitner, Stephan; Zoeller, Joachim E.; Kreppel, Matthias (Journal of Cranio-Maxillofacial Surgery, 2015)
Lingual undercuts are common in the edentulous mandible and pose the risk of perforating the lingual cortical bone during insertion of dental implants, which may lead to hemorrhage or infections of the parapharyngeal space. The aim of our study was to determine the occurrence and extent of lingual undercuts in the molar and premolar/canine region of the mandible.We analyzed 716 cross-sections of the edentulous molar region and 215 cross-sections of the edentulous first premolar/canine region. Mandibular morphology was classified into a U-configuration (undercut), P-configuration (parallel), and C-configuration (convex), depending on the shape of the alveolar ridge. Depth of the lingual concavity, concavity angle, and further parameters were measured to describe the mandibular morphology.Lingual undercuts had a prevalence of 68% in the molar region. The prevalence was significantly higher in the second molar region (90%) than in the first molar region (56%). A deep position of the inferior alveolar nerve close to the basal cortical bone was significantly associated with the presence of lingual undercuts.Lingual undercuts are a frequent in the edentulous mandible. Cross-sectional analysis of three-dimensional radiographs provides the opportunity to determine a lingual undercut and to prevent complications of perforating the lingual cortical bone.
EVALuna2:24824